Aesthetics of Religion A Connective Concept - Grieser, Alexandra 1965-; Johnston, Jay (Berlin/Boston De Gruyter, 2017)
Sinceits founding by Jacques Waardenburg in 1971, Religion and Reason has been a leading forum for contributions on theories, theoretical issues and agendas related to the phenomenon and the study of religion. Topics include (among others) category formation, comparison, ethnophilosophy, hermeneutics, methodology, myth, phenomenology, philosophy of science, scientific atheism, structuralism, and theories of religion. From time to time the series publishes volumes that map the state of the art and the history of the discipline
Intro -- Foreword -- Table of Contents -- What is an Aesthetics of Religion? From the Senses to Meaningâand Back Again -- List of Figures -- PART I. Fields and Topics -- Grasping the Formless in Stones: The Petromorphic Gods of the Hindu PaÃ±cÄyatanapÅ«jÄ -- Religion, Literature, and the Aesthetics of Expressionism -- Screening the Father of Lights: Documentary Film and the Aesthetics of the Nonfictional in Contemporary Religion -- The Literary Aesthetics of Religious Narratives: Probing Literary-Aesthetic Form, Emotion, and Sensory Effects in Exodus 7â11 -- PART II. History and Politics -- Below the Horizon of Meaning: Figuration, Disfiguration, Transfiguration -- The Performative Knowledge of Ecstasy: Jane E. Harrisonâs (1850â1928) Early Contestations of the Textual Paradigm in Religious Studies -- What Does a Reformed City Look Like? â Changes in Visible Religion During the Reformation in Bremen -- Standing, Not Walking â The Hieratic as a Key Term of an Anthropologically Based Aesthetics of Religion -- PART III. Comparison and Transfer -- Blue Brains: Aesthetic Ideologies and the Formation of Knowledge Between Religion and Science -- Aesthetic Dimensions and Transformative Dynamics of Mimetic Acts: The Veneration of Habib-i Neccar Among Muslims and Christians in Antakya, Turkey -- Aestheticisation and the Production of (Religious) Space in Chennai -- Moving Religion by Sound: On the Effectiveness of the NÄda-Brahman in India and Modern Europe -- PART IV. Concepts and Theories -- Esoteric Aesthetics: The Spiritual Matter of Intersubjective Encounter -- Aesthetics of Immersion: Collective Effervescence, Bodily Synchronisation and the Sensory Navigation of the Sacred -- The Governance of Aesthetic Subjects Through Body Knowledge and Affect Economies. A Cognitive-Aesthetic Approach
Religion in the Flesh: Non-Reductive Materialism and the Ecological Aesthetics of Religion -- PART V. In Conversation: Essays About the Connectivity of an Aesthetics of Religion -- Subjects and Sense-Making -- Consumer Culture and the Sensory Remodelling of Religion -- Social Aesthetics, Atmosphere and Proprioception -- Semiotics and Aesthetics: Historical and Structural Connections -- The Artificiality of Aesthetics: Making Connections on the Erie Canal -- Authors Biographies -- Index
Keywords: Religion and civil society; Electronic books